Unmet need of contraceptives amongst the married women of reproductive age group: a study in a coastal belt of Bangladesh - Dutta, Palas; Debnath, Sumon Chandra; Ghosh, Kinkar (Bangladesh Medical Journal, 2019)
This cross-sectional study was conducted with an objective to assess the unmet need of contraceptives among married women of reproductive age at Assasuni Upazila (coastal area) in Satkhira District during the period from January to December 2016. A total of 222 participants (married women) were included in the study. The mean (± SD) age of the respondents was 27.9 ± 6.2 years and about half (45.9%) of the respondent’s marriage age were between 15 and 17 years. Most of the (85.6%) women were housewives and more than half (50.9%) belongs to a nuclear family. Most of the respondents (94.6%) were not currently pregnant and about one-fourth (25.7%) of them experienced with previous pregnancies. About ninety percent of the outcomes of last pregnancy were live-births. More than two-thirds (80.2%) were using contraceptives. More than two-fifth of the respondents was using the oral pill and 17.6% of their husband’s using condoms as a contraceptive. Among 222 respondents, 13.5% had the unmet need of contraceptives. Unmet need comprises who were not using any method of contraception due to husband’s opposition, did not know, opposition from other family members and no menstruation after last childbirth, (6.3%, 5.0%, 1.3% and 0.9%, respectively). Unmet need of contraceptive is high despite an extensive family planning program in Bangladesh. It is necessary for the governments to come up with strategies, which can reduce unmet needs of contraceptive, especially among coastal area. Bangladesh Med J. 2018 Jan; 47 (1): 37-40